Przyczynek do rozważań nad przynależnością dziedzinową nauk o polityce - Wallas, Tadeusz (My University, 2015)
Since the number of academic specializations and disciplines has consistently been increasing, it has become necessary to supplement present classifications and categorizations, as well as come up with new ones, on a regular basis. Therefore, it has become feasible to distinguish a new branch of science as well as to assign the existing disciplines to different branches. It is owing to such a process that political sciences have been reassigned in Poland. Before September 30, 2011, political sciences had been categorized as the humanities, but later on they were encompassed by a new branch of social sciences, created as a result of the division of the humanities. I adopt the thesis that this decision was substantially justified since, given current legal status quo, political sciences as a discipline have more in common with other disciplines assigned to social sciences than the humanities. Additionally, by way of developing a new register of disciplines, the administrative divisions in Polish science were to a large extent aligned with the classification of branches and disciplines adopted by the OECD, UNESCO and Eurostat, which will facilitate the internationalization of academic collaboration. The above organizations and institutions, and – consequently – some of their member states, have already divided the humanities, sometimes also named social sciences, into two separate branches: social sciences and humanities. In order to justify the above‑mentioned thesis it was necessary to determine how academic specialization, discipline, branch and field of science are perceived today; to indicate the determinants of divisions in science and basic criteria for such divisions; to attempt to define the specific nature of the humanities versus social sciences; and to present the factors confirming the relation of political science to the latter category.
Contribution to the considerations on the assignment of political sciences to a scientific field
Keywords: political sciences; nauki o polityce; humanities; nauki humanistyczne; classification of sciences; klasyfikacja nauk; social sciences; nauki społeczne; categorization of political sciences as a branch of science; dziedzinowa przynależność nauk o polityce